Roads, trade, and growth: PPML evidence on Pakistan's vegetable export performance - Khan, Humayun; Yan, Zeng; Chunjie, Qi (Frontiers in Sustainable Food Systems, 2025)
The China-Pakistan Economic Corridor (CPEC) with the objective of enhanced infrastructural development, trade cooperation, and regional economic prosperity is a pivotal project. This study investigates the patterns and prospects of CPEC on vegetable exports in Pakistan. We analyze a panel dataset of Pakistan's vegetable export destinations countries from 2003 to 2021. We preferred the Poisson Pseudo Maximum-Likelihood (PPML) as the state-of-the-art technique in the trade gravity framework for estimation. The findings revealed that Pakistan's economic activities with the countries linked with CPEC have grown. The total length of the road as a proxy of road infrastructure is a key factor in determining Pakistan's vegetable export performance. The importer countries' GDP and the legacy of colonial links also enhance Pakistan's vegetable export performance. Distance, contiguity, and language negatively affect Pakistan's vegetable exports. Additionally, rising domestic vegetable consumption has reduced export capacity while increasing imports. Moreover, we also found an inverse relation of vegetable exports to the countries that were part of Pakistan in the past. Finally, based on the findings of our estimates we put forth suggestions to respond to the vegetable trade deficit of Pakistan.